Researching families and communities [ social and generational change - Edwards, Rosalind (Relationships and resources, 2008)
Researching Families and Communities: Social and Generational Change explores the concepts and perspectives that guide research and the methods used to explore change during the last half of the 20th century and into the new millennium. It highlights the complexities of continuities alongside change, the importance of the perspectives that shape investigation, and the need to engage with situated data.